THE RELATIONSHIP BETWEEN NURSES' CHARACTERISTICS AND CONTINUING PROFESSIONAL DEVELOPMENT - Arlina Dhian Sulistyowati; Istianna Nurhidayati; Nur Isnaini Sudarsono (Universitas Airlangga, 2023)
Introduction: Continuing Professional Development (CPD) is a professional development activity intended to maintain and improve nurses' knowledge, skills, and competencies so that they are able to update and develop their skill set. One of factors which influence the continuing professional development is the individual characteristics of nurses including age, gender, length of service, and employment status. The current study aims to determine the relationship between nurses' characteristics and the continuing professional development of executive nurses. Methods: This study employed a Quantitative Correlation with a Cross-sectional design. The sample consisted of 157 nurses selected using a cluster random sampling technique. Meanwhile, the data analysis was performed utilizing the Chi-Square test. Results: The findings revealed that 65% of nurses successfully met their continuing professional development. The Chi-Square test result indicate that no relationship was found between age, gender, length of service, and employment status with the continuing professional development of executive nurses. Meanwhile, a relationship was found between education and continuing professional development of executive nurses. Conclusions: According to the nurses' characteristics, only their education demonstrated a correlation with the continuing professional development of executive nurse.